(untitled) (Stamford Journal of Pharmaceutical Sciences, 2010)
Dipeptidyl peptidase-IV (DPP-IV) could serve as a potential biomarker in monitoring the disease progression and improvement on treatment. To investigate fasting & post prandial response of DPP-IV enzyme as indirect marker of incretin response failure after chronic treatment with metformin in type 2 diabetes. The study included twelve nondiabetic subjects, ten patients with glycosylated hemoglobin values (6-8%) and fifteen patients with glycosylated hemoglobin greater than 8 % of type-2 diabetes patients of either sex with metformin treatment above 3 years were recruited. Fasting and post prandial DPP-IV levels were calculated. HbA1c was used to assess diabetes status. DPP-IV activity (fasting) in type 2 diabetic subjects with HbA1c > 8 % was significantly higher DPP-IV (44.67 ± 2.19 U/l) than in non diabetic subjects (24.39 ± 3.97 U/l). A significant correlation between DPP-IV (fasting / post prandial) and HbA1c (r = 0.821 & r = 0.732, P< 0.01) was observed in both diabetic (HbA1c 6-8, HbA1c < 8) patients. Hyperglycemia induces significant increase in serum DPP-IV activity in fasting condition and might contribute to the reduction in active glucagon like peptide-1(GLP-1) in type 2 diabetic subjects. In normal subjects during post prandial condition, there is sudden increase followed by decrease of GLP-1 due to cleavage of GLP-1 to as substrate of DPP-IV is seen as upsurge of DPP-IV. This response was lacking in diabetic patients with high HbA1c indicates indirectly metformin failure to secrete GLP-1. High fasting level and decreased post prandial of DPP-IV may indicate drug failure in type-2 diabetes mellitus. Key words: Type 2 diabetes; metformin; DPP-IV; HbA1c; GLP-1. DOI: 10.3329/sjps.v2i2.1698 Stamford Journal of Pharmaceutical Sciences Vol.2(2) 2009: 81-85